Effect of functionalised silver nanoparticle on the elastic constants and ionic transport of a nematic liquid crystal. Issue 12 (26th September 2019) - S. J., Shivaraja; Gupta, R. K.; Kumar, Sandeep; V, Manjuladevi
ABSTRACT: Addition of nanomaterial into pure nematic liquid crystals (NLCs) leads to improvement in the various physical properties of the liquid crystal (LC) host. Doping of nanomaterials affects the local molecular arrangement of the LC molecules. Here, we present the results of our investigation on the effect of functionalised silver nanoparticles (f-AgNPs) on the physical properties of the rod-shaped NLC, 4-trans-pentyl-cyclohexyl cyanobenzene (5PCH). The dielectric constant, threshold voltage, elastic constants, birefringence and conductivity measurements were performed on pure 5PCH and its f-AgNPs doped nanocomposites as a function of temperature in planar cell. The magnitude of dielectric anisotropy, elastic constants and birefringence in nanocomposites were enhanced with increasing concentration of f-AgNPs indicating enhancement of order parameter in the nematic medium. Threshold voltage decreases with increasing concentration of f-AgNPs. Both parallel and perpendicular components of conductivity decrease with increasing concentration of f-AgNPs due to the absorption of ion by the doped f-AgNPs. This observed decrease in conductivity in nanocomposites is further confirmed by calculating the ion transportation number and time of flight. The ion transport number i.e ionic contribution present in the LC cell was found to be 0.966 in pure 5PCH, whereas 0.830 in 0.5 wt% of f-AgNPs nanocomposite of 5PCH. Graphical Abstract: